(3GdeYLe aj eTJHg CSGej GdoeMOKjfs - (3GdMGaX CHh GdaVd YHjO Gddg Hf YHO Gddg Hf CMeO Hf eMeO Hf jhSa GdgQhjs ((3CHhHcQ Hf Ydj Hf ESeGYjd GdHgfSj GdCfUGQj GdTGaYj s)
(3ChdgG (B:s
(3aEf HYV ENhGfj HCUHgGf Sdeg Gddg , SCdfi Gf CLeY dge aUhdkG aj eYQaI CSGej eTGjN ef fbdI GdMOjK hQhGI GdCNHGQ ef cHGQge GdPjf jQhj Yfge s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B149 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(624) s
Keywords: (3GdJGQjNs